Visceral leishmaniasis in a patient with direct positive coombs hemolytic anemia:: a public health alert - Holodniak, Ana Catarina da Paz; Silva, Liliany Mara Rodrigues da; da Silva, Henaiana Solanne Lucien; Cavalcante, Maria de Nazaré Miranda; Koga, Rosemary de Carvalho Rocha (Revista Arquivos Científicos (IMMES), 2023)
Visceral leishmaniasis (VL) is a zoonosis with high morbidity and mortality. Endemic in tropical and subtropical regions. Autoimmune Hemolytic Anemia (AIHA) is a clinical condition in which autoantibodies bind to antigens located on the erythrocyte surface. The coexistence of the hematological picture of AIHA is rarely observed in patients with VL. The symptomatic manifestation of the case can become a dilemma, as the evolution to a more severe condition, due to intrinsic factors of the patient. In this report, we present the case of a patient with VL infection associated with a hematological picture of AIHA, with clinical manifestations of asthenia, weight loss, pyrexia, night sweats, jaundice, choluria, faecal acholia, nausea, vomiting, pancytopenia and hepatosplenomegaly. This article aims to present a case report, as a form of alert to health authorities, about the clinical-epidemiological impact of the VL-AIHA association in the area of circulation of the VL transmitting vector.